Arquitetura de software e de hardware para o aprimoramento da experiência de uso de jogos de tiro virtuais no estilo point-and-click - Pinheiro, Émerson Bezerra (2024)
Shooting games have evolved significantly over their history. However, the integration of light weapons into these games has seen limited development in the past decade. This study introduces a laser capture solution to improve interaction in traditional point-and-click shooting games. Through the description of an architectural framework and the development of a seamless solution bridging player and game, this approach adapts gameplay and offers a fresh user experience without necessitating alterations to the original game design. Four diverse games were employed to assess the effectiveness of this solution: two commercially available third-party titles and two specifically crafted for testing purposes. Various types of weapons were explored, including toys, Airsoft replicas, and 3D-printed models, with consistently impressive results. Notably, there was no discernible compromise in gaming performance—all tested titles maintained stable operation at 60 FPS. Moreover, participants in the experiment, evaluated through focused group analysis, expressed genuine enthusiasm for the immersive experience, novel gameplay, and seamless integration, reporting no perceptible delay between firing and corresponding mouse input generated by the system.